Long term diazotrophic cultivation induces phycobiliprotein production in Anabaena variabilis IMU8 - Fadhil Haddad, Mohammed; Dayioglu, Tugba; Nalbantoglu, Barbaros; Cakmak, Turgay (TECH SCIENCE PRESS, 2019)
Cyanobacteria are considered as a sustainable feedstock for the production of biochemically active compounds such as phycobiliproteins (PBPs). In this study, the impact of nitrogen (N) and phosphorus (P) availability on PBP production of N-free acclimated Anabaena variabilis IMU8 was analyzed. Upon isolation and identification, the cyanobacterium has been maintained in N-free BG-11 medium for more than 20 months. For experimentation, the strain was incubated in N-replete, N-depleted, N-P-depleted BG-11 medium. Long-term diazotrophic cultivation of A. variabilis IMU8 resulted in elevated PBP productivity with a limited impact on growth. When compared to N-depleted ones, N supply stimulated a slight induction of growth and total saccharide production, but total protein content did not change while PBP production decreased. On the other hand, N-P-depletion resulted in decreased growth rate along with reduced total protein and PBP production while rapid induction of total saccharide production was recorded. Fourier transform infrared spectroscopy results refer that membrane-bound oligosaccharides may have regulatory roles for PBP production in A. variabilis IMU8 during long term diazotrophic cultivation.
Keywords: Cyanobacteria; Nitrogen; Phosphorus; Phycobiliprotein; C-PHYCOCYANIN; DEFICIENCY; MICROALGAE; Life Sciences & Biomedicine - Other Topics